Presença de distorções cognitivas em propagandas brasileiras - Rosa, Renata Rezende (2014)
This research aimed to examine the presence of cognitive distortions in national advertisements, proposing a secondary objective that cognitive therapists pay attention to this presence as a possible influencer in the therapeutic process, in particular, on the steps of reframing and restructuring of thoughts and beliefs using this type of material to teach pacientes about cognitive distortions and their consequences. The hypothesis presented is that cognitive distortions are present in advertisements. In this sense, were selected and transcribed two advertisements, aired nationally on public television, the first related to cosmetics, beauty and personal care market, while the second belongs to the insurance industry. The method used to verify the presence of distortions was proof of judges. Participated in this research 6 judges who are professionals specializing in cognitive behavioral therapy, with academic performance and / or clinical area. The judges of this research were five participants female (83%) and one male participant (17%) with a mean age of 30 years (SD 6.47) and trained on average 7 years (SD 6.88 ). The sample was composed of psychologists who have completed specialized in Cognitive Behavioral Therapy on average 4 years (SD 4.89), which act in the clinical area and / or are teachers in higher education. The judges reviewed the transcript (verbal and non-verbal content) of advertisements, followed by a table on which ten distortions were described whose presence meant to be seen. The distortions were presented: A) all or nothing thinking; B) catastrophizing; C) disqualifying the positive; D) lettering; E) magnification / minimization; F) mental filter; G) mind reading; H) overgeneralization; I) customization; J) statements like I should or I should. Judges should read and judging whether the distortions were present in the transcribed advertisement, could still choose an option according to which there would be no distortion in the presence of transcribed propaganda. The data collected were analyzed using the Binomial Test. The statistical result points to the presence of cognitive distortion \"all or nothing thinking\" the first advertisement. Advertising in the insurance industry, the statistical analysis indicates the presence of distortion \"catastrophizing.\" The technical categorization, registration and reframing of thought occupy important role in the process of Cognitive Therapy. The analysis of the presence of cognitive distortions in advertisements is the possibility of Cognitive Therapists for more heed if one related to the promotion and maintenance of maladaptive thoughts and beliefs present in various contexts in which people are embedded aspect, which may include their considerations in therapy, greater notice regarding the impact of advertising on the maintenance of the disorders or complaints submitted by individuals in treatment. Moreover, further studies aimed at understanding the relationship between the distortions and propaganda can contribute to an advertising regulation that considers aspects related to cognitive processing and cognitive distortions avoid spreading the actions of the media.